Entrepreneurial Engagement of Students in Startup Creation: Case of the University of Bejaia - Aicha BAGDI; Nawal KHEBBACHE (Journal of Excellence for Economics and Management Research, 2026)
Reflection on entrepreneurship constitutes a vast research field. The objective of this study is to contribute to the understanding of student entrepreneurship, specifically the creation of startups.In this perspective, we first aimed to build a theoretical framework for the research. Secondly, we examined and presented the context of the study, highlighting its particularities. Finally, we conducted a survey among one hundred and eleven (111) final year students from Algerian universities.Data collection was carried out using an exploratory quantitative approach among final year students (L3, M1, M2) from various Algerian universities using a Google Forms questionnaire, and data were analyzed using SPSS software.The study reveals the positive impact of entrepreneurship training on the entrepreneurial intention of students, who appear to be quite favorable to the creation of startups, particularly in the fields of commerce and digitalization. However, they face significant obstacles: lack of funding, practical experience, and unawareness of supporting organizations